2015
DOI: 10.4012/dmj.2015-085
|View full text |Cite
|
Sign up to set email alerts
|

Enamel cracks evaluation —A method to predict tooth surface damage during the debonding

Abstract: The objective of this in vitro study was to evaluate the effect of the enamel cracks on the tooth damage during the debonding. Measurements of the cracks characteristics (visibility, direction, length, and location) were performed utilizing a scanning electron microscopy (SEM) technique and mathematically derived formulas (x=h/30, l=n*x) before and following the removal of mechanically retained metal and ceramic brackets. The likelihood of having greater extent enamel defects was higher for the teeth with pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Enamel reduction that might occur during debonding may compromise tooth resistance, creating enamel cracks and fractures in combination with increasing surface roughness [12,13]. This may lead to plaque accumulation resulting in caries development.…”
Section: Discussionmentioning
confidence: 99%
“…Enamel reduction that might occur during debonding may compromise tooth resistance, creating enamel cracks and fractures in combination with increasing surface roughness [12,13]. This may lead to plaque accumulation resulting in caries development.…”
Section: Discussionmentioning
confidence: 99%
“…As previously demonstrated by other Authors (14), the presence of a C-factor particularly unfavorable, as in the case of the inlays with a good marginal fit, the shrinkage stress developed from thin composite cement thickness, is efficiently dissipated by the deformability (compliance) of the substrate to which it is adherent. In our experimental model both the C-factor and the compliance were particularly favorable because the modulus of elasticity (E) of the acrylic resin (2.65 GPa) is much lower than dentin (18.3 GPa) (2,8,11,14). Thus our finding may be attributable to the high compliance of the substrate that is able to compensate the resulting shrinkage stress.…”
Section: Discussionmentioning
confidence: 99%
“…The development of this tensile force, along the adhesive interface, can result in deformation of the cavity walls if the adhesion force is strong enough, conversely it determines the separation of the restoration from the tooth. If the thickness of the residual dental tissue is thin, it may also occur of the enamel fracture (enamel crack) when this latter is not sufficiently supported by the dentin (11). This phenomenon, together with the flow that the composite undergoes, during the setting reaction, at the level of the free surface of the restoration, which is not subject to adhesion, limits the negative effects of stress but does not cancel them completely (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…1. The buccal enamel surfaces of all the teeth included in the study (both from the younger and older age group) were examined employing SEM (TM-1000, Hitachi, Tokyo, Japan) 9,12,13) . The SEM was operated at 15 kV, at ≤5×10 −2 Pa (electron gun vacuum) and at ~30-50 Pa (specimen chamber vacuum).…”
Section: Methodsmentioning
confidence: 99%
“…EMCs, quite often visible by the naked eye, may jeopardize the integrity of the enamel, cause stain and plaque accumulation on the rough fractured surface, thus increasing susceptibility to carious lesions and compromising the appearance of the teeth [6][7][8] . Studies have shown that the bracket removal procedure is related with the EMCs increase and formation of new EMCs [9][10][11][12][13] . Various methods, such as transillumination, staining, ultrasound, or optical coherence tomography (OCT) have been described in the literature for EMCs detection [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%